Phytochemical analysis of citrus maxima and its effect on male reproductive system in high-fat diet induced sprague dawley rats / Farah Amna Othman ... [et al.] - Othman, Farah Amna; Syed Mohamad, Syarifah Faezah; Sabarudin, Nur Aalia Adilah; Ajit, Nurul Nadia (Universiti Teknologi MARA Cawangan Pahang, 2018)
Present study was designed to evaluate phytochemical constituents, hypoglycemic effect and the juice effect of Citrus maxima on sperm quality. In phytochemical screening, the juices were tested for availability of reducing sugar, flavonoid, antraquinone, tannins, terpenoid, saponin and alkaloid. In animal study, the rats were subjected to high fat diet for 6 weeks to induce obesity and hyperglycemic. The rats were then divided into 3 groups (n=6); control, HFD and CM groups. The results obtained demonstrated that C. maxima juice possessed reducing sugars, terpenoids, and saponins. Body weight in CM group increased significantly (p≤0.05) throughout the treatment period. Sperm count was higher in the CM group as compared to HFD group, even though the differences were not significant. HFD group showed significant decrease (p≤0.05) in progressive motility (PM) sperms, highest percent in non-progressive motility (NPM) and non motile (NM) sperms compared to control group. HFD and CM groups showed significant decreased in normal sperm compared to control group, where CM group showed better result compared to HFD group. HFD displayed significant decrease (p≤0.05) in blood glucose level compared to control group. It was concluded that the adverse effects of HFD on male reproductive system can be reversed by treatment with C. maxima juices, where it also displayed antihyperglycemic and anti-obesity effects